Achieving equity in Crunch&Sip®: a pilot intervention of supplementary free fruit and vegetables in NSW classrooms. (24th April 2017) - Hector, Debra; Edwards, Shelley; Gale, Joanne; Ryan, Helen
Abstract : Issue addressed: Anecdotal evidence from teachers in Western Sydney Local Health District (WSLHD) indicated that many primary school children are regularly unable to participate in the Crunch&Sip ® (C&S) program (breaks during class time to eat fruit and/or vegetables and drink water) as they do not bring produce from home. Actual reach of the program may therefore be currently overestimated, and inequitable. This study examined the feasibility, acceptability and efficacy of providing school children supplementary, fresh free produce in supporting equitable participation in C&S. Methods: Free fruit and vegetables were provided for 10 weeks to four schools in a socioeconomically‐disadvantaged area in Western Sydney. WSLHD sourced the produce at a discounted rate and storage and distribution was arranged in partnership with industry. Schools determined methods of allocation to children who did not have fruit or vegetables for the C&S break. Pre‐ and late‐intervention (Week 9) classroom surveys provided quantitative data of intervention efficacy. Qualitative methods were used with key school persons to explore barriers and enablers to implementation. Results: Participation of children in C&S increased significantly from 46.7% pre‐intervention to 92.0% in Week 9. The proportion of children bringing fruit or vegetables from home also increased significantly, from 46.7% to 54.0%. Schools perceived the supplementary strategy to be highly feasible and acceptable. Conclusion: Expansion of this equity strategy warrants consideration, although issues of sustainability would need to be addressed. The criteria for 'full implementation' should include high proportional participation by students in participating classes. So what?: Establishing a system by which schools in disadvantaged areas can supplement their C&S program would effectively increase access to fruit and vegetables among those children most at need. Abstract : In NSW primary schools, classroom breaks for children to consume fruit or vegetables and drink water rely on parental provision of produce. This pilot intervention showed that provision of free produce to previously non‐participating children was required to ensure equitable reach of the C&S program.